THE HIGH-PRESSURE STRUCTURE OF KAERSUTITE AND ITS GEOLOGICAL IMPORTANCE - Zhu X.P.; Qin S.; Han B.F.; Liu J.; Li X.D.; Wu X.; Wu Z.H. (My University, 2004)
The in-situ high-pressure structure of natural kaersutite, obtained from the mantle xenolith in alkali basalt of southwestern Tianshan in Xinjiang, has been studied using synchrotron radiation energy dispersive X-ray diffraction and diamond anvil cell at the pressures up to 25.4 GPa. At room temperature, the lattice constants a, b, c of kaersutite are compressed continuously with increasing pressure and at the pressure of 18. 9 GPa, a phase transition occurs probably due to the dehydration. Considering the geological occurrence of kaersutite, the experimental results indicate that kaersutite could be stable with rather a depth in the upper mantle, and it must be a rapid process when kaersutite is brought to the earth's surface. In addition, this research would be potentially helpful for the understanding of high-pressure behaviors of other Ti-bearing minerals.
Keywords: kaersutite